2021
DOI: 10.3390/educsci11040172
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and ICT. Bibliometric Study on Digital Literacy in Higher Education

Abstract: The scientific production of digital literacy at the university level published in the Scopus database is analyzed, with a special emphasis on studies on tourism due to the relevance of information and communication technology (ICT) in said professional sector. For this, a bibliometric study of a pertinent sample is undertaken using a mixed methodology and based on a series of variables related to formal and content aspects. The last variable, reserved for the academic field under study, directly addresses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 97 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…Throughout the literature review, no bibliometric analysis of the proposed topic has been found. Therefore, this research was designed following other bibliometric analyses carried out in the tourism context (Caldevilla-Domínguez et al, 2021;Della Corte et al, 2019). To collect the data, the Scopus database of Eselvier-origin dated March 2004was used.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the literature review, no bibliometric analysis of the proposed topic has been found. Therefore, this research was designed following other bibliometric analyses carried out in the tourism context (Caldevilla-Domínguez et al, 2021;Della Corte et al, 2019). To collect the data, the Scopus database of Eselvier-origin dated March 2004was used.…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis has gained popularity in science education research in recent years: The scientific output on topics such as physics problem solving [22], STEAM education [23], digital literacy in higher education [24], scientific literacy [25], the role of virtual reality in computer science education [21] or the linking behaviour in the physics education research co-authorship network [26] were-among others-analysed bibliometrically. That is the case because bibliometric analysis is helpful for (a) uncovering and mapping cumulative scientific research foci and (b) producing a thorough overview of scientific output and its development over time in the research area under investigation [27].…”
Section: Methodsmentioning
confidence: 99%
“…According to Atoy et al (2020), "people with high levels of digital literacy are more active in social affairs; are better able to express their opinions; and are able to search and understand desired information, express, share opinions or thoughts freely, and have a better understanding of those of others" (p. 1016). Higher education plays a key role in acquiring the skills necessary for students to be properly integrated into the professional context; however, despite the constant adaptation of new technologies and methods of social interaction across industries and academic disciplines, many higher education institutions have not yet fully embraced digital literacy as a fundamental literacy (Caldevilla-Domínguez et al, 2021). The guiding motivation for changing the way students learn is that they should be better prepared for college, career, and civic engagement in a pluralistic and democratic society that puts considerable emphasis and trust into the notion of ''informed decision-making'' by all.…”
Section: Digital Literacy As a Complex Skillmentioning
confidence: 99%